High Fluoride Intake and Low Calcium Alongwith Genetic Predisposition May Lead to Bone Weakness and Deformation - Verma, Mahendra Kumar; Singh, Ravinder Pal; Tyagi, Manoj G (International Journal of Innovative Research in Medical Science, 2019)
Fluoride affects bone strength, by replacing hydroxyl ions in bone crystals to form fluoroapatite, and increasing both the osteoblast and osteoclast activity. Daily intake of naturally fluoridated water, is inevitable in many areas and countries throughout the world, it remains a major health issue as it has been suggested that fluorides may paradoxically aggravate osteoporosis and increase osteoporotic fractures and several epidemiological studies have been published showing that there is an increased rate of bone fractures i.e mostly hip fractures in older people in living in fluoridated areas. This study was carried out to ascertain the fact that high fluoride intake and low calcium may have on bone deformities in patients.